How Does Drinking Water Quality Affect Women’s Pregnancy Outcomes in Colombia? - Birkhölzer Vaquero,Laura (2025)
The study investigates the relationship between drinking water quality and birth outcomes in Colombia, focusing on early neonatal mortality and low birth weight. Using nationally representative Demographic and Health Survey data, the study combines logistic, multilevel and spatial analysis to assess individual-level and geographic determinants of neonatal health. The results show that mothers exposed to poor drinking water quality face significantly higher risks of early neonatal mortality. Geographic analysis indicates that variation in pregnancy outcomes is driven by differences at the community level rather than broader regional divisions and reveals disparities in water quality and neonatal outcomes across Colombia’s watershed regions. These findings highlights the need for integrated water and neonatal health policies.